Estrategias de arteterapia para el cuidado de enfermería en niños con Trastorno de Déficit de Atención e Hiperactividad (2024)
The document addresses the narrative review of the literature on art therapy strategies for children diagnosed with Attention Deficit and Hyperactivity Disorder (ADHD), focusing on the role of nursing with different strategies to improve children’s symptoms and help in their quality of life. The different stages in which the review was carried out are described, frem the identification of problems to the presentation of the final report of the benefits obtained from the different strategies that were carried out and the improvement of each child who participated in the interventions, the importance of ethical considerations is also mentioned. 11 relevant literature were selected which meet the criteria established for the review, highlighting art therapy as a non-pharmacological method and evidencing a significant improvement in symptoms such as care, hyperactivity and impulsivity of children diagnosed with ADHD. In addition, the various forms of art therapy such as music therapy, narrative, architecture and coloring games were recognized, demonstrating their effectiveness in the short, medium and long term.